Giving Green Bean Spice Juice as an Alternative Therapy for Anemia to Young Women in The Working Area of Puskesmas Kota Selatan, Gorontalo City - Endah Yulianingsih; Ika Suherlin; Sri Sujawaty (Institute of Computer Science (IOCS), 2021)
The health of a young woman as a prospective mother and as the nation's successor needs to be a major concern. Adolescents are an age group that is prone to anemia. Anemia in young women will have an impact on reproductive health. Mung beans are plants that can grow almost everywhere in Indonesia. Green bean spice juice is one of the preparations that can help increase hemoglobin levels in the blood. The purpose of this study was to analyze the administration of green bean spice juice as an alternative therapy for adolescent girls who experience anemia. This type of research is pre-experimental with a one-group pretest-posttest design approach. The results of this study showed that the mean hemoglobin before giving green bean spice juice (pretest) was 8.73 and the average after giving green bean spice juice (posttest) was 11.03. This means that giving green bean spice juice can increase the hemoglobin level of the respondent with an Asym Sig value of 0.000 (p <0.05), thus Ho is rejected, meaning that there is an effect of giving green kajang spice juice on increasing hemoglobin levels in young women in the work area of ​​the Kota Selatan City Health Center. Gorontalo. The conclusion is that there is a significant effect of giving mung bean spices juice on increasing blood hemoglobin levels in adolescent girls with anemia in the working area of ​​Puskesmas Kota Selatan Kota Gorontalo